2022
DOI: 10.1002/qre.3077
|View full text |Cite
|
Sign up to set email alerts
|

Statistical process control of overdispersed count data based on one‐parameter Poisson mixture models

Abstract: The Poisson distribution is a discrete model widely used to analyze count data. Statistical control charts based on this distribution, such as the c$c$ and u$u$ charts, are relatively well‐established in the literature. Nevertheless, many studies suggest the need for alternative approaches that allow for modeling overdispersion, a phenomenon that can be observed in several fields, including biology, ecology, healthcare, marketing, economics, and industry. The one‐parameter Poisson mixture distributions, whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This approach was adopted as a precautionary measure to mitigate the effects of overdispersion. In view of this concept, Jesus et al [21] suggested in their study that handling overdispersion with the Poisson mixture distribution would eliminate the problem and increase the ARL performance. However, the charts they deal with are not EWMA charts as similar to Boaventura et al [27], but for the c and u charts developed for attribute data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach was adopted as a precautionary measure to mitigate the effects of overdispersion. In view of this concept, Jesus et al [21] suggested in their study that handling overdispersion with the Poisson mixture distribution would eliminate the problem and increase the ARL performance. However, the charts they deal with are not EWMA charts as similar to Boaventura et al [27], but for the c and u charts developed for attribute data.…”
Section: Discussionmentioning
confidence: 99%
“…By capitalizing on the equality between the variance and mean of a Poisson distribution, we make a substitution of α i instead of σ 2 i , leading to the derivation of the formula presented in Equation (21).…”
Section: Poisson Mixture Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saghir and Lin 15 provided an excellent overview on different approaches to construct control charts for count data that are either over‐ or under‐dispersed. Recently, several control charts have been proposed for count data using the BerG distribution, 16 the Touchard distribution, 17 and one‐parameter Poisson mixture distributions 18 to account for over‐ or under‐dispersion in count data.…”
Section: Introductionmentioning
confidence: 99%
“…Saghir and Lin, 9,10 among others, further extended that control chart to EWMA and CUSUM charts, respectively. Other existing control charts for monitoring under-or over-dispersed count data used the Katz distribution family, 11 the generalized Poisson model, 12 the BerG distribution, 13 the Touchard distribution, 14 and one parameter Poisson mixture models, 15 to list a few. Readers are referred to Saghir and Lin 16 for an overview of control charts for monitoring under-or over-dispersed count data.…”
Section: Introductionmentioning
confidence: 99%